The ED50 and ED95 of oxytocin infusion rate for maintaining uterine tone during elective caesarean delivery: a dose-finding study - Xiao Wei Qian; Dan M. Drzymalski; Chang Cheng Lv; Fei He Guo; Lu Yang Wang; Xin Zhong Chen (BMC, 2019)
Abstract Background The 90% effective dose (ED90) of oxytocin infusion has been previously estimated to be 16.2 IU h− 1. However, bolus administration of oxytocin prior to the infusion may decrease the infusion dose required. The aim of this study was to estimate the ED95 for oxytocin infusion after a bolus at elective caesarean delivery (CD) in nonlaboring parturients. Methods We performed a randomized, triple blinded study in 150 healthy termparturients scheduled for elective CD under epidural anaesthesia. After delivery of the infant and i.v. administration of 1 IU oxytocin as a bolus, Participants were randomized to receive oxytocin infusion at a rate of 0, 1, 2, 3, 5, or 8 IU h− 1, to be given for a total of 1 h. Uterine tone assessed by the blinded obstetrician as either adequate or inadequate. Secondary outcomes included estimated blood loss (EBL), requirement for supplemental uterotonic agents, and development of side effects. Results The 95% effective dose (ED95) of oxytocin infusion was estimated to be 7.72 IU h− 1 (95% confidence interval 5.80-12.67 IU h− 1). With increasing oxytocin infusion rate, the proportion of parturients who needed rescue oxytocin bolus or secondary uterotonic agents decreased. No significant among-group differences in the EBL and oxytocin-related side effects were observed. Conclusions In parturients who receive a 1 IU bolus of oxytocin during elective cesarean delivery, an infusion rate of oxytocin at 7.72 IU h− 1 will produce adequate uterine tone in 95% of parturients. These results suggest that the total dose of oxytocin administered in the postpartum period can be decreased when administered as an infusion after oxytocin bolus.